A Hidden Ideological Scheme under New Secularism: Explaining a Peak of Islamphobia in Quebec (2013-2014). Issue 1 (1st October 2015) - ,
Abstract : This paper offers a description of the context of the recent growth of Islamophobia in Quebec, and it submits a hypothesis on the process responsible for it. In the first part, we use the concept of "mute zone" from the social representation theory to advance a theoretical hypothesis based on a first sight analysis. We argue that some elements from an ideological victory of far right narratives invested the social representation of secularism, that they reveal themselves as a "mute zone" acting in periphery of the theme of secularism, and, accordingly, that they act as a sleeping ideological scheme, here, favoring Islamophobia. In the second part, we pursue the analysis further to show how this peripheral scheme appeared within the narrative of different actors and groups supporting a ban on religious conspicuous signs, from the right side to the left side of the political spectrum.